Mesoscale Simulation of Natural Convection in Square Cavity Driven by Discrete Two Source-Sink Pairs On One Sidewall - Mohd Irwan, Mohd Azmi; Nazri, Md Daud; Fudhail, Abdul munir; Suhaimi , Misha (2011)
Lattice Boltzmann method (LBM) was applied to predict fluid flow and heat transfer characteristics of natural convection in a two-dimensional square cavity driven by two discrete source-sink pairs on one vertical sidewall. The size of sources and sinks was L/4. The arrangement of the sources and sinks were alternately located. Simulations were conducted at Rayleigh number 1000 to 100000. The characteristics were represented by streamlines and isotherms. It was found that the solution is comparatively acceptable with other previous study applying conventional approach.